Pengaruh Profesionalisme Dan Motivasi Berprestasi Terhadap Kinerja Pegawai Kantor Badan Penanggulangan Bencana Daerah Kabupaten Sikka - Yulia Apriliani Ayu Astuti Pondeng; Imanuel Wellem; Yosef Tonce (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This study aims to : (1) determine the description of employee performance, professionalism, and achievement motivation; (2) analyze the effect of professionalism and achievement motivation employee performance either partially or simultaneously. The population in this study were 38 employees of the Sikka Regency Regional Disaster Management Agency. Because the population is limited, this research was carried out by means of a census or saturated sampling. Data were collected through questionnaires and analyzed using deccriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is done through the F test and t test. The results of the descriptive analysis show that the variables of employee performance, professionalism and achievement motivation are categorized as good. The results of the t-test statistics show that partially the variables of professionalism and achievement motivation have a positive and significant effect on employee performance. The statistical results of the F test show that simultaneously the variables of professionalism and achievement motivation have a significant effect on employee performance. The results of the determination analysis show that the two independent variables in this study are able to explain the variation in the ups and downs of the performance of the employees of the Sikka Regency Regional Disaster Management Agency Office of 29.25%.